Pengaruh Persepsi Mahasiswa, Minat Mahasiswa, Dan Penghargaan Finansial Terhadap Pemilihan Karir Sebagai Auditor: Studi Kasus Pada Mahasiswa Jurusan Akuntansi Universitas Hindu Indonesia - Ni Putu Melani Putri; Sang Ayu Putu Arie Indraswarawati; Ni Wayan Yuniasih (UNHI Press, 2026)
The purpose of this study is to ascertain how student perspective, interest, and financial gain affect the decision to become an auditor.With a student population of 379, this study was carried out at the Hindu University of Indonesia Denpasar. Using the proportionate stratified random sampling technique and the Slovin formula, a sample size of 194 students from the 2019–2022 class was chosen. Observation techniques, literature reviews, and questionnaires with a five-choice Likert scale were used to collect data. Following an evaluation of the instrument's validity and reliability using SPSS software, multiple linear regression analysis and conventional assumption tests were conducted. The results of the study show that students' decisions to pursue professions as auditors are considerably and favorably influenced by perception, student interest, and financial reward.